2019
DOI: 10.1177/2333392819861246
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Wait Times and Patient Satisfaction: Findings From Primary Health Centers in the Kingdom of Saudi Arabia

Abstract: Background: It is no doubt that longer wait times can affect patient care and patients’ willingness to seek health-care services. Not only does this disrupt the continuity of treatment and care, but it also negatively impacts patient outcomes. During the past few years, the concept of patient satisfaction has become a vital component in assessing the delivery and efficiency of care. Patient satisfaction is a performance indicator that measures the extent to which patient is content and satisfied with the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 18 publications
1
39
2
1
Order By: Relevance
“…Regarding the second principal component of service delivery, the results showed that promptness of service delivery and short waiting time do not necessarily affect customer satisfaction positively. Among studies in the healthcare eld, which is close to the eld of government, some show that waiting time in hospitals has an effect, especially a negative effect, on patient satisfaction (Alrasheedi et al 2019). By contrast, previous studies have shown that it is not the waiting time itself-or 'objective waiting time'-that affects patient satisfaction but the way the patient waits or their 'waiting environment' (Pruyn and Smidts 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the second principal component of service delivery, the results showed that promptness of service delivery and short waiting time do not necessarily affect customer satisfaction positively. Among studies in the healthcare eld, which is close to the eld of government, some show that waiting time in hospitals has an effect, especially a negative effect, on patient satisfaction (Alrasheedi et al 2019). By contrast, previous studies have shown that it is not the waiting time itself-or 'objective waiting time'-that affects patient satisfaction but the way the patient waits or their 'waiting environment' (Pruyn and Smidts 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has summarized the domains used for patient satisfaction measurement in Saudi Arabia, which includes communication attributes, relational conduct, technical skill, personal qualities, availability, and accessibility [12]. Meanwhile, many empirical studies have been conducted to measure patient satisfaction in different countries, such as England [13], Pakistan [14,15], China [16,17,18,19,20], Germany [21], Saudi Arabia [22], the U.S. [23], Canada [24], Italy [25], and South Africa [26]. Among these studies, multifarious measures were employed and numerous determinants of patient satisfaction were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Patient plays the pivotal role of giving the intrinsic value for any healthcare facilities in terms of quality, perfection, integrated institutional and professional work (Saha, et al, 2008). It has a significant role in determining the health outcomes and in the quality of health-care services provided by any health-care organization, since that, patients' satisfaction is one of the most important purpose and strategic goal for all healthcare providers (Alrasheedi, et al, 2019). Hospitals and healthcare systems that invest in programs to detect how patients evaluate their experiences will gain valuable information toward transformational changes in care delivery and services (Ferrand, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While in the other hand patient's dissatisfaction could result in a loss of long-term gains because of decreased retention, fewer repeat visits, and conveyance of dissatisfaction with the organization to others. Patient's satisfaction is a performance indicator that measures the extent to which patient is contented with the level of care provided by health-care institutions and providers (Alrasheedi, et al, 2019). It also may represented as the degree to which anticipated goals have been accomplished with inclusion of both cognitive and emotional facets and relation to previous experiences, expectations, and social networks (Verma & Jauhari, 2014).…”
Section: Introductionmentioning
confidence: 99%